Preliminary results of a cohort study of induction chemotherapy-based treatment for locally recurrent rectal cancer. Issue 4 (23rd November 2017) - van Zoggel, D. M. G. I.; Bosman, S. J.; Kusters, M.; Nieuwenhuijzen, G. A. P.; Cnossen, J. S.; Creemers, G. J.; van Lijnschoten, G.; Rutten, H. J. T.
Abstract: Background: A significant number of patients treated for locally recurrent rectal cancer have local or systemic failure, especially after incomplete surgical resection. Neoadjuvant treatment regimens in patients who have already undergone preoperative (chemo)radiotherapy for the primary tumour are limited. The objective of the present study was to evaluate the influence of a neoadjuvant regimen incorporating induction chemotherapy (ICT) in patients with locally recurrent rectal cancer who had preoperative (chemo)radiotherapy for the primary cancer or an earlier local recurrence. Methods: Patients were treated with a sequential neoadjuvant regimen including three or four cycles of 5-fluorouracil and oxaliplatin-containing chemotherapy. When no progressive disease was found at evaluation, neoadjuvant treatment was continued with chemoradiation therapy (CRRT) using 30 Gy with concomitant capecitabine. If there was a response to ICT, the patient was advised to continue with systemic chemotherapy after CRRT as consolidation chemotherapy while waiting for resection. These patients were compared with patients who received CRRT alone in the same time interval. Results: Of 58 patients who had ICT, 32 (55 per cent) had surgery with clear resection margins, of whom ten (17 per cent) exhibited a pathological complete response (pCR). The remaining 26 patients had 23 R1 and three R2 resections. In 71 patients who received CRRT, a similar rate of R0 (35 patients) and R1 (36) resection was found ( P = 0·506), but only three patients (4 per cent) had a pCR ( P = 0·015). Conclusion: The incorporation of ICT in neoadjuvant regimens for locally recurrent rectal cancer is a promising strategy.